The sanctuary of Zeus Krezimos in Metropolis in Ionia - Serdar Aybek; Boris Dreyer; Christina Sponsel (Gephyra, 2018)
The sacred site of Zeus Krezimos, just in front of the rocky part of the northern slope of the Metropolis acropolis, is considered to be the first cult center discovered in the ancient city. Although the exact location of the cult center of Ares, the god of the city, is unknown, it is thought to be on the acropolis in an exceptional situation. The only cult centers older than dedicated to Ares are the sacred caves of the Mother Goddess, whose name was given to the city. In these sacred caves located in Uyuzdere, 5 km outside the city, the Mother Goddess was worshiped until the advent of Christianity.During the excavation consequent upon the stylobate blocks discovered in 2015, in excavations at the sacred site of Zeus Krezimos, the discovery of an inscribed columns, a part of an altar and a sculpture base caused an excitement. It is not yet certain whether the columns had capitals. The inscribed sections on the column drums surrounding the courtyard are arranged in a way to face the courtyard. The base diameter of the columns erected on the surface of the stylobate extends out at some places, suggesting the possibility of a second function. The courtyard is covered in local limestone slabs. As a result of a trench opened in this area, it was understood that the floor was in-filled with rubble and marble pieces. In addition, rooms that were thought to have been used in cult ceremonies in the northern and eastern parts of the sanctuary, which is located behind the columns, were uncovered. Further, a certain area of the main rock was cut in a regular fashion and the fact that this is interconnected with the architectural structure is an example of a construction technique that has not been found elsewhere in Metropolis to date. As a result of the studies conducted on the inscriptions, it was understood that this area was a cult area dedicated to Zeus Krezimos. This cult area was known to exist at Metropolis but its exact location was unknown. The discovery of the Zeus Krezimos cult area in Metropolis is of great importance, inasmuch as the cults of Hera and Ares worshipped in Metropolis, which are also known from inscriptions but their locations have not yet been found. The fact that this sacred area was built right in front of a large rocky area and integrated with the rock also shows the cult at Metropolis was a continuation of the ancient tradition in Anatolia of worshiping the gods and goddesses on mountains and in rocky high lands. In studies conducted on the inscriptions, this cult was also understood to have had a connection with water due to the hydrobaphos attribute recorded of one of the civil servants working in the cult. This provides us with clues about a ceremonial ritual associated with rocks and the spring water from them. Today, although there is no water source in this rocky area, it is thought that such a source of water emerged from the rocky area at the time when the cults were still active. Consequently, the cult with Zeus Krezimos epithet is thought to have been a local cult associated with fertility and abundance.The fact that the Zeus Krezimos cult was specific to Metropolis is supported by the epigraphic evidence. The inscribed column drums in the sacred area carry lists of the names of the priests serving here. In past years, inscribed column drums relating to the Ares cult known to exist in the city were found, and on these drums the name lists of people serving in the cult area as well as those in the sanctuary of Zeus Krezimos were included. The cult of Zeus Krezimos was behind that of Ares in the hierarchy, but nevertheless families were active in it, those whose family heads were ambitious for themselves and their relatives put them into positions within the cult. There existed personal connections to other cults, some at the level of the priests, more often on the level of the Odrogos. The women of the families – with the function of priestess, of the hydrobaphos and the female servant – were subordinate, but still prominent. Also in this cult no wife was allowed in the position of the priestess. The priest “Hermas” and the hydrobaphos are propria of the cult.